Cold electroweak baryogenesis with Standard Model CP violation - Tranberg, Anders; Hernández Canseco, Andrés; Konstandin, Thomas; Schmidt, Michael G. (Physics letters, 2010)
We study a mechanism that generates the baryon asymmetry of the Universe during a tachyonic electroweak phase transition. We utilize as sole source of CP violation an operator that was recently obtained from the Standard Model by integrating out the quarks.
Gesehen am 22.12.2023